Practice guidance for the use of terlipressin for liver cirrhosis–related complications. (May 2022) - Qi, Xingshun; Bai, Zhaohui; Zhu, Qiang; Cheng, Gang; Chen, Yu; Dang, Xiaowei; Ding, Huiguo; Han, Juqiang; Han, Lei; He, Yingli; Ji, Fanpu; Jin, Hongxu; et al.
Background: Liver cirrhosis is a major global health burden worldwide due to its high risk of morbidity and mortality. Role of terlipressin for the management of liver cirrhosis–related complications has been recognized during recent years. This article aims to develop evidence-based clinical practice guidance on the use of terlipressin for liver cirrhosis–related complications. Methods: Hepatobiliary Study Group of the Chinese Society of Gastroenterology of the Chinese Medical Association and Hepatology Committee of the Chinese Research Hospital Association have invited gastroenterologists, hepatologists, infectious disease specialists, surgeons, and clinical pharmacists to formulate the clinical practice guidance based on comprehensive literature review and experts' clinical experiences. Results: Overall, 10 major guidance statements regarding efficacy and safety of terlipressin in liver cirrhosis were proposed. Terlipressin can be beneficial for the management of cirrhotic patients with acute variceal bleeding and hepatorenal syndrome (HRS). However, the evidence regarding the use of terlipressin in cirrhotic patients with ascites, post-paracentesis circulatory dysfunction, and bacterial infections and in those undergoing hepatic resection and liver transplantation remains insufficient. Terlipressin-related adverse events, mainly including gastrointestinal symptoms, electrolyte disturbance, and cardiovascular and respiratory adverse events, should be closely monitored. Conclusion: The current clinical practice guidance supports the use of terlipressin for gastroesophageal variceal bleeding and HRS in liver cirrhosis. High-quality studies are needed to further clarify its potential effects in other liver cirrhosis–related complications.